Exercise cardiac MRI unmasks cardiac dysfunction in childhood and adolescent cancer survivors with reduced cardiopulmonary fitness. (25th November 2020) - Foulkes, S; Costello, B; Howden, E.J; Janssens, K; Dillon, H; Toro, C; Fraser, S.F; Daly, R.M; Elliott, D.A; Conyers, R; La Gerche, A
Abstract: Background: Young cancer survivors are at increased risk of impaired cardiopulmonary fitness (VO2peak) and heart failure. Assessment of exercise cardiac reserve may reveal sub-clinical abnormalities that better explain impairments in fitness and long term heart failure risk. Purpose: To investigate the presence of impaired VO2peak in pediatric cancer survivors with increased risk of heart failure, and to assess its relationship with resting cardiac function and cardiac reserve Methods: Twenty pediatric cancer survivors (aged 8–24 years) treated with anthracycline chemotherapy underwent cardiopulmonary exercise testing to quantify VO2peak, with a value <85% of predicted defined as impaired VO2peak. Resting cardiac function was assessed using 3-dimensional echocardiography, with cardiac reserve quantified from resting and peak exercise heart rate (HR), stroke volume index (SVi) and cardiac index (CI) using exercise cardiac magnetic resonance imaging. Results: 12 of 20 survivors (60%) had impaired VO2peak (97±14% vs. 70±16% of age and gender predicted). There were no differences in echocardiographic or CMR measurements of resting cardiac function between survivors with normal or impaired VO2peak. However, those with reduced VO2peak had diminished cardiac reserve, with a lesser increase in CI (Fig. 1A) and SVi (Fig. 1B) during exercise (Interaction P=0.001 for both), whilst the HR response was similar (Fig. 1C; P=0.71). Conclusions: Resting measures of cardiac function are insensitive to significant cardiac dysfunction amongst pediatric cancer survivors with reduced VO2peak. Measures of cardiopulmonary fitness and cardiac reserve may aid in early identification of survivors with heightened risk of long-term heart failure. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Heart Foundation